Airport surface access in the UK: A management perspective - Budd, Thomas; Ison, Stephen; Ryley, Tim (Elsevier, 2011)
Air passenger traffic in the UK has increased significantly over the last 30 years, and is forecast to continue to grow for the foreseeable future. A key associated challenge for airports involves the management of airport surface access. Currently, airport surface access in the UK is heavily reliant on trips by private car, which has resulted in congestion on local road networks and raised levels of pollution from vehicle emissions. The paper offers an airport management perspective on airport surface access in the UK. Semi-structured interviews with key personnel responsible for surface access management at 14 UK airports revealed a wide variety of surface access issues and management policies. The need to reduce the share of journeys made by private car is identified as a key issue, with a particular focus on reducing ‘kiss-and-fly’ journeys for passengers. Whilst reducing private car journeys may yield environmental benefits, such strategies are largely at odds with substantial commercial pressures to maximise the revenue potential of airport parking.
Keywords: Surface access; Airport; Management; Environment